Pay with Confidence : A Thematic Analysis of User Intentions and Perceptions on Third-Party and Banking Payment Apps - Pahari, Subhajit; Manna, Atanu; Biswas, Debasish (Indian Journal of Finance, 2023)
Purpose : Mobile payment and banking applications have transformed traditional banking systems, gaining immense popularity among consumers. This study aimed to compare the usefulness and reliability of third-party payment and banking apps from the users’ perspective. Methodology : Using a qualitative research approach, we conducted 30 interviews with users from different backgrounds, employing purposive sampling. Thematic analysis was conducted using Atlast.ti software to accomplish the study’s objectives. Findings : The study identified the primary themes of utility and reliability into seven sub-themes. User-friendliness, accessibility, features and rewards, and trust and convenience were the four principal sub-themes that were highly related to usefulness. There was a strong correlation between these features and customers’ plans to use third-party payment apps. On the other hand, customer support, stability, and security were closely related to the reliability theme and significantly helped customers of banking and payment apps. Practical Implications : The study’s findings suggested that third-party payment apps need to improve their reliability concerns, while banking payment apps need to enhance their usability features to compete in the market. Financial institutions, policymakers, and academicians could utilize these findings to design payment apps that meet customers’ needs and expectations, gaining a competitive edge in the payment app market. Originality : This research was the first to focus on and compare third-party payment and banking payment apps based on users’ perceptions and use intentions. Above all, this study provided valuable insights into the features that customers consider crucial in payment and banking apps. Enhancing these features could lead to a better user experience and foster customer loyalty.